2018
DOI: 10.1111/ina.12449
|View full text |Cite
|
Sign up to set email alerts
|

Association of size-fractionated indoor particulate matter and black carbon with heart rate variability in healthy elderly women in Beijing

Abstract: Associations between size-fractionated indoor particulate matter (PM) and black carbon (BC) and heart rate variability (HRV) and heart rate (HR) in elderly women remain unclear. Twenty-nine healthy elderly women were measured for 24-hour HRV/HR indices. Real-time size-fractionated indoor PM and BC were monitored on the same day and on the preceding day. Mixed-effects models were applied to investigate the associations between pollutants and HRV/HR indices. Increases in size-fractionated indoor PM were signific… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(12 citation statements)
references
References 51 publications
(66 reference statements)
2
9
1
Order By: Relevance
“…However, the results were different for cardiac autonomic function. It was observed that increases in PM and BC were associated with decreases in HF, LF and SDNN, similar to previous findings among young adults and the elderly (Chen et al, 2007;Dong et al, 2018;Pan et al, 2018). Yet the potential benefits from reduced particulate pollution might be overcast by increased NAI.…”
Section: Pm0supporting
confidence: 89%
“…However, the results were different for cardiac autonomic function. It was observed that increases in PM and BC were associated with decreases in HF, LF and SDNN, similar to previous findings among young adults and the elderly (Chen et al, 2007;Dong et al, 2018;Pan et al, 2018). Yet the potential benefits from reduced particulate pollution might be overcast by increased NAI.…”
Section: Pm0supporting
confidence: 89%
“…Our previous studies have estimated the associations of indoor PM pollution and health effects. 10,11,36 Using the iron tracer method, 38 This study suggested that PM 2.5,os was associated with BP levels of healthy elderly adults during the heating season and with pulmonary function during the non-heating season, whereas PM 2.5,is was linked with pulmonary function in COPD patients during the heating season.…”
Section: Discussionmentioning
confidence: 97%
“…10,11,36 Using the iron tracer method, 38 DBP, diastolic blood pressure; FEV 1 , forced expiratory volume in first second; PEF, peak expiratory flow; PP, pulse pressure; SBP, systolic blood pressure; SD, standard deviation. Our previous studies have estimated the associations of indoor PM pollution and health effects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13 Low-grade, chronic inflammation is believed to exacerbate cardiovascular disease, 14 while dysfunction of the autonomic nervous system manifests as irregularities in HR, heart rhythm, and BP. 15,16 HR and HRV are regulated by the sympathetic and parasympathetic (vagus nerve) parts of the autonomic nervous system. Autonomic imbalance is a major contributor to severe ventricular arrhythmias and sudden cardiac death.…”
Section: Discussionmentioning
confidence: 99%